Normal reference ranges of ductus venosus doppler indices in the period from 14 to 40 weeks' gestation - Tongprasert,F. (S. Karger AG, 2015)
Objective: To construct reference ranges of ductus venosus (DV) Doppler indices in normal singleton pregnancies. Methods: A cross-sectional study was conducted on low-risk singleton pregnancies with accurate gestational age, and normal fetuses were enrolled into the study. Measurements of DV Doppler indices were determined by experienced sonographers. Poor quality images were excluded. Results: A total of 640 fetuses underwent DV measurements, ranging from 13 to 30 for each gestational week. The relationship between gestational age and DV Doppler indices was not linear. The best-fit regression equations are as follows: preload index = (5.061 - 0.4882) × exp (-0.211 × GA) + 0.4882; peak velocity index for veins = (7.498 - 0.5609) × exp (-0.2184 × GA) + 0.5609; pulsatility index for veins = (17.9 - 0.6053) × exp (-0.2512 × GA) + 0.6053; systolic/atrial wave ratio = (300 - 2.124) × exp (-0.3649 × GA) + 2.124. Notably, during the period from 14 to 20 weeks' gestation, all of the four indices rapidly decreased and they were relatively stable or slightly decreased after that. The nomogram tables for various percentile ranges were constructed. Conclusion: A nomogram for DV Doppler indices for each gestational week during the period from 14 to 40 weeks' gestation was established. These reference ranges may be a useful non-invasive tool for evaluation of fetal cardiac function. Copyright © 2011 S. Karger AG, Basel.